(untitled) (Jurnal Geomine, 2021)
The study area is located in Wumbubangka, North Rarowatu District, Bombana Regency, Southeast Sulawesi Province. This study aims to identify the types of metamorphic rocks and metamorphic facies found in the study area. The research method used consists of literature study, field sampling, laboratory analysis and data interpretation. The results showed that the lithology of the study area generally consisted of mucosite schists and marble. Muscovite schist has a texture in the form of lepidoblastic, schistose structure, while marble has a residual texture and a non-foliated structure. The mineral composition consists of calcite, chlorite, quartz, muscovite, biotite, glucofan and opaque minerals. The metamorphic facies of metamorphic rocks in the study area are green schist facies characterized by the presence of muscovite, chlorite, biotite, calcite and quartz minerals. The facies of this green schist are interpreted to form at a temperature of 300 ° C-500 ° C.